¿Por qué los acuerdos internacionales de inversiones limitan los procesos de transformación productiva en países en desarrollo? algunas respuestas desde la experiencia de los países andinos con la Unión Europea - GARCÍA ÁLVAREZ, Santiago (Papeles de Europa, 2011)
When developing countries apply international investment agreements like a main way to attract FDI, they are betting incorrectly because such agreements are only able to affect the general framework of national politics, but not to the economic determinants that are finally those with preponderance to attract FDI. However, this kind of strategy includes several engagements to protect FDI and to implement liberalization policies. As a result, states losses ability to guide FDI to national objectives related to development en general and to productive transformation en particular way.